CCL20 and Beta-defensin 2 Production by Human Lung Epithelial Cells and Macrophages in Response to Brucella abortus infection - Hielpos, María Soledad (2015)
Both CCL20 and human β-defensin 2 (hBD2) interact with the same membrane receptor and display chemotactic and antimicrobial activities. They are produced by airway epithelia in response to infectious agents and proinflammatory cytokines. Whereas Brucella spp. can infect humans through inhalation, their ability to induce CCL20 and hBD2 in lung cells is unknown. Here we show that B. abortus induces CCL20 expression in human alveolar (A549) or bronchial (Calu-6) epithelial cell lines, primary alveolar epithelial cells, primary human monocytes, monocyte-derived macrophages and the monocytic cell line THP-1. CCL20 expression was mainly mediated by JNK1/2 and NF-kB in both Calu-6 and THP-1 cells. CCL20 secretion was markedly induced in A549, Calu-6 and THP-1 cells by heat-killed B. abortus or a model Brucella lipoprotein (L-Omp19) but not by the B. abortus lipopolysaccharide (LPS). Accordingly, CCL20 production by B. abortus-infected cells was strongly TLR2-dependent. Whereas hBD2 expression was not induced by B. abortus infection, it was significantly induced in A549 cells by conditioned media from B. abortus-infected THP-1 monocytes (CMB). A similar inducing effect was observed on CCL20 secretion. Experiments using blocking agents revealed that IL-1β, but not TNF-α, was involved in the induction of hBD2 and CCL20 secretion by CMB. In the in vitro antimicrobial assay, the lethal dose (LD) 50 of CCL20 for B. abortus (>50 μg/ml) was markedly higher than that against E. coli (1.5 μg/ml) or a B. abortus mutant lacking the O polysaccharide in its LPS (8.7 ug/ml). hBD2 did not kill any of the B. abortus strains at the tested concentrations. These results show that human lung epithelial cells secrete CCL20 and hBD2 in response to B. abortus and/or to cytokines produced by infected monocytes. Whereas these molecules do not seem to exert antimicrobial activity against this pathogen, they could recruit immune cells to the infection site.